A pause with the Verses of Bahrain in The Holy Quran - Kambal, Awad Mohammed Ahmed (Journal of Islamic Sciences, 2021)
The essence of this topic is the conversation about (The Verses of Bahrain) mentioned in the Book of God Almighty, as these verses are mentioned five times in the Qur’an. The honorable one, and that is why this research was the subject of five investigations. The researcher spoke in those investigations about the verses in which the word (Bahrain) came in Deuteronomy, The researcher dealt with the many benefits and blessings of these seas, as their fresh and salty waters have many benefits, and countless and countless goodies, and there is the great divine wisdom in the isthmus and the interdicted stone, which was mentioned in those verses, and the differences of scholars in the past and present in that barrier, and how modern science has interpreted that. In the course of the research, the researcher mentioned the living creatures that live inside these seas, as well as extracting pearls and coral from the depths of these vast oceans, and seeing the large ships that pierce the water in an enormous way back and forth, all with the power of God Almighty. As for the method and nature of the study, it is represented in the inductive analytical method, by collecting the verses in question, explaining and interpreting them according to the pleasure of the Almighty God from ancient and modern sources, and this method is what researchers follow in such research. The most important results of this research can be summarized as follows: The seas have a great variety of importance and that is why they took a good space from the Holy Book. And that the Signs of the Sea include a scientific miracle that modern science recently discovered. That the Prophet, may God’s prayers and peace be upon him, did not explain such verses, because the time has not yet come for them. That such verses clearly indicate the greatness and enormous power of God.